Money and capital in economic development - McKinnon, Ronald I. (Washington, Brookings Institution, 1973)
This book makes a major contribution to the analysis of economic development. The author both establishes that the main causes of underdevelopment reside in economic repression by restricted, uncompetitive money, goods, and foreign exchange markets and explains why some 'orthodox' measures of reform have failed to bring economic efficiency and growth. McKinnon advances theoretical arguments and empirical evidence to suggest that a more effective strategy for economic growth would proceed from a thorough liberalisation of financial markets and the lifting of restraints on foreign trade.
Includes bibliographical references.
lje 20/09/2018
Loans
Keywords: Economic development; Finance; Capital